Pengaruh Etos Kerja Dan Kemampuan Sumber Daya Manusia Terhadap Kinerja Pegawai Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Sikka - Yuliana Ngole; Walter Obon; Yustina Olivia Da Silva (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
This research aimed to (1) determine the description of employee performance, work ethic and capabilities of Human Resources at the Civil Registry and Population Office of Sikka Regency, and (2) determine the influence of work ethic and Human Resources capabilities on employee performance both partially and simultaneously. The population in this research were 55 employees who worked at the Civil Registry and Population Office of Sikka Regency. The sample used the saturated sample technique. Data was collected through census or saturated sampling. Data were collected through questionnaires and analyzed using a descriptive method, namely multiple linear regression. Hypothesis testing through the F test and t-test. The findings of the descriptive analysis revealed that the variables of employee performance, work ethic, and Human Resources capabilities were quite good. The results of the t-test showed that the work ethic variable had no significant influence and the ability of Human Resources had a significant value on employee performance. The results of the F test showed that the variables of work ethic and Human Resources capabilities simultaneously had a significant influence on employee performance. The coefficient of determination was 0.477 which indicated the contribution of the work ethic and Human Resources variables on employee performance of the Civil Registry and Population Office of Sikka Regency was 22.7%